Evaluating the effectiveness of public finance used for social protection of internally displaced persons - Yuriy Bilan; Halyna Yurchyk; Natalia Samoliuk; Halyna Mishchuk (Public and Municipal Finance)
The increasing number of internally displaced persons (IDPs) in wartime Ukraine leads to growing problems in social protection funding. Under these circumstances, the evaluation of the effectiveness of public finance use is of increasing importance. The study aims to evaluate the effectiveness of public finance for internally displaced persons’ social protection, adapting the KPI methodology for analysis on the national level. The effectiveness is considered following the OECD approach as the extent to which the intervention achieved its objectives and results. At macrolevel of research, the integral indicator was developed based on indicators of input (financing of social protection programs), output (involvement of IDPs in social programs), activity (funding per recipient and multiplicative effect in GDP growth), mechanism (administrative costs for achieving results), and control (effectiveness of IDPs’ social protection compared to other demographic groups). Thirty indicators in total were used (e.g., budgetary funding allocated for housing assistance; budget expenditures on staff salaries of the authorities responsible for certain programs; coverage rate of unemployed IDPs receiving vocational training). The essential distance from the maximum level of expected results (1.0) allows concluding the low effectiveness in this area of public finance use: from 0.330 in 2020 to 0.668 in 2023. Gaps are evident in each direction, especially in input performance (the highest value did not exceed 0.370). The best results were achieved in housing funding and employment governance. The proposed approach is useful for analyzing gaps and identifying opportunities to improve the management of other social programs.